Besedni red v kontekstu členitve po aktualnosti - Žele, Andreja (Jezik in slovstvo, 2025)
Slovenian word order is based on the division of the sentence according to the principles of topicality and focus. It is shaped by the contextual topicality at any given moment and the genre-stylistic needs of specific messages. The connection between the sentence structure and the thematization-rematization of the entire message is expressed in such a way that a change in the sentence structure, in its topic and focus, primarily alters the communicative perspective of the utterance, without any stylistic emphasis or markedness. In terms of structural thematization and communicative rematization at the level of the entire message, and the triad of topic–transition–focus at the sentence level, there is a mutual contextual (co-)textual interaction between the communicative perspective of the individual sentence and the informational saturation of the entire message. By taking into account the entire communicative context, a schema is created within the sentence, moving from left to right: theme proper – theme (with a tendency towards a theme proper or towards a diatema) – diatema – transition proper – transition – rheme – rheme proper. In this sequence, the degree of communicative dynamism (CD) increases and intensifies primarily within the sentence, but also within smaller non-sentential syntactic units. The highest degree of CD is achieved by components that express new information. We distinguish between fully integrated and partially integrated word-order positions in the sentence, in which the functional sentence perspective is shaped by combinations of specific communicative elements/components. From both a semantic perspective and a sentence intonation standpoint, the initial and final positions are emphasized and thus obligatorily occupied. The current functional perspective of the sentence, regarding sentence structure and positional filling, is generally tied to the specific text and context.
Keywords: besedni red; communicative elements; communicative positions; context; členitev po aktualnosti; functional sentence perspective; kontekst; Slovenian language; slovenščina; sporočanjske prvine; sporočanjski položaji; word order